2016
DOI: 10.1080/14739879.2016.1142772
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of appraisal: a critical (re)view of the literature

Abstract: It has been acknowledged that little is known about the impact of general practice (GP) appraisal on clinical and professional practice, as may be demonstrated by identifiable or 'hard' outcomes, and further, that the way in which appraisal informs professional development is unclear. In spite of this acknowledgement and the existence of a substantial number of studies about GP appraisal, to date an overview of the field of enquiry which maps what is known, has been lacking. In this leading article we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Appraisals may have less perceived benefit in interaction with patients and colleagues than other aspects of appraisal although the percentage in our study was less than that in a previous paper [1] which may suggest that this aspect reflects changes in the RCGP guidance on appraisal in 2016 in elevating quality over quantity in the evidence submitted at annual appraisal. The burden of preparing for appraisal has been noted in previous studies [2,5,9,10] was reported as too high by both cohorts in our study.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 53%
See 1 more Smart Citation
“…Appraisals may have less perceived benefit in interaction with patients and colleagues than other aspects of appraisal although the percentage in our study was less than that in a previous paper [1] which may suggest that this aspect reflects changes in the RCGP guidance on appraisal in 2016 in elevating quality over quantity in the evidence submitted at annual appraisal. The burden of preparing for appraisal has been noted in previous studies [2,5,9,10] was reported as too high by both cohorts in our study.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 53%
“…Scallan et al [10] identified surveys of appraisal as a 'snapshot' of data and that a clear link between the process of appraisal and the impact on clinical practice/ quality of care had not been established and cautioned against the roll-out of appraisals to other professions before effectiveness had been demonstrated. We support this conclusion and while our survey does not provide the evidence, it does confirm the need to reconsider the value of appraisals when many doctors find the process burdensome.…”
Section: Implications For Practicementioning
confidence: 99%
“…Despite the increased importance of the appraisal process to the medical profession, and the change in nature of medical appraisal, there is little understanding of the theory of how and why appraisal is supposed to improve doctors' performance. Scallan et al's scoping review of the literature on appraisal found that to date the literature has mainly focused on: ‘engagement’ from the perspective of the doctor being appraised; exploration of different models of appraisal (internal versus external appraisal, peer and practice appraisal, and appraisal for revalidation); the benefits of appraisal; GPs' perceptions of the problematic link between appraisal and performance assessment or revalidation; administrative and management issues; and developing appraisers' skills.…”
Section: Introductionmentioning
confidence: 99%
“…One of the goals of graduate medical education is to train physicians to critically appraise the literature so they can practice evidence‐based medicine 28 . Both the quality and quantity of scholarly activity being pursued is highly variable among physicians and evidence suggests that more education is needed to improve accurate appraisal of the literature, including and especially in the area of spin 29,30 …”
Section: Discussionmentioning
confidence: 99%